2021
DOI: 10.1080/09540105.2021.1956434
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of black rice and blueberry regulate immunity system through regulation of MAPKs, NF-kB in RAW264.7 macrophage cells

Abstract: Bioconversion can enhance the functionality of efficacy. We made bioconversion material with black rice (Oryza sativa L.) and blueberry (Vaccinium crymbosum L.), using Lactobacillus plantarum (call BB). In this study, BB investigated anti-inflammatory and immune-boosting effects through immune system control. Therefore, we investigated the efficacy of BB in the presence and absence of LPS (Lipopolysaccharide). In the presence of LPS, the bioconversion material inhibited nitric oxide (NO) production from LPS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Due to its high nutritional content and other health advantages, the production and consumption of black rice are on the rise. Black rice has more antioxidants than blueberries (6).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high nutritional content and other health advantages, the production and consumption of black rice are on the rise. Black rice has more antioxidants than blueberries (6).…”
Section: Introductionmentioning
confidence: 99%
“…Blueberry fruit has high levels of anthocyanins and other nutritional and healthcare-related functional substances that have strong antioxidant activity (Wu et al, 2022b). These substances can prevent cardiovascular disease (Cassidy et al, 2016), regulate immune ability (Kim et al, 2021), and intestinal microbial balance (Si et al, 2021), alleviate visual fatigue (Yao et al, 2015), and reduce blood glucose levels (Tian et al, 2021). These edible and health functions of blueberries have resulted in the continual expansion of their cultivation areas and scope globally (Wu et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Bioconversion is the conversion of organic materials from natural product by biological processes [6]. In the food industry, bioconversion is used to produce feed and energy using food waste, and to improve bioactivity and bioavailability [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Among the lactic acid bacteria used for bioconversion, Lactiplantibacillus plantarum has been used to convert flavonoid glycosides in Cudrania tricuspidata leaves into its aglycone, and to convert ginsenoside Rb2 and Rb3 in red ginseng to ginsenoside Rd [10,11]. It has also been reported that immune system regulation, whitening, and antioxidant activity of various natural products are enhanced through bioconversion using L. plantarum [6,12].…”
Section: Introductionmentioning
confidence: 99%